Designing a Cognitive-Behavioral Coping Training Package with the Stress of Infertility and Its Effectiveness on Hope in Infertile Women - Samaneh Ghobadi; Keivan Kakabraee; Mahmoud Goudarzi (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk)
Introduction: For many people, infertility is a prominent crisis and cause of mental stress that causes many unfavorable psychological reactions. The purpose of the research is to design a cognitive-behavioral coping training package with the stress of infertility and its effectiveness on the hope of infertile women. Methods: The present study was conducted using a mixed method using the qualitative part, content analysis type, and the quantitative part, semi-experimental, in the pre-test-post-test-two-month follow-up design with the control group. The statistical population of this research was infertile women referring to infertility centers and gynecology and infertility specialists in Kermanshah in 2022. A sample of forty women was selected as a sample using the purposeful sampling method and replaced in two groups (experimental and control) in a simple random manner. Data were collected from Newton et al.'s infertility stress questionnaire (1999) and Schneider's Hope (1991). The data was analyzed using a content validity test and repeated measurement variance analysis tests. Results: The designed educational package was valid and adequate. The findings showed a significant difference between pre-test, post-test, and follow-up in the component of hope, and this difference continued until the follow-up stage. Conclusions: The educational package on cognitive-behavioral coping with the stress of infertility of infertile women can be used to reduce the stress and increase the hope of infertile women.